PENGGUNAAN MEDIA PEMBELAJARAN PUZZLE RABU PADA MATA PELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK - Handayani, Berkah (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
Pancasila education is one of the subjects in the independent curriculum with material content that tends to be difficult and of little interest to students, so that the learning that occurs tends to be boring for students. The purpose of this study is to use the “Puzzle Rabu” media to improve student motivation and learning outcomes. This study uses a quasi experimental method. Data collection techniques in this research are observation, tests and interviews. Observations were carried out to observe students' learning motivation, tests were carried out to determine students' learning outcomes before or after using learning media, and interviews were carried out to obtain data in the form of statements from students about the learning they were taking part in. The results of this research show an increase in students' learning motivation from 33% to 83.5% as well as an increase in learning outcomes from an average score of 55 to 84.44. This proves that the use of “Puzzle Rabu” media in Pancasila Education subjects regarding cultural diversity can increase student motivation and learning outcomes.